Pemanfaatan Akses Aplikasi Belajar pada Proses Pembelajaran di Indonesia di Masa Pandemi Covid-19 - Nur Fauziah (STAI Auliaurrasyidin Tembilahan, 2021)
The Covid-19 pandemic that hit Indonesia has a very significant impact on education. The spread of that virus is not only in Indonesia but throughout the world, so many learning processes run down. Educational institutions have been closed due to concerns about the Covid-19 expansion. The spread of the virus is very fast, but learning must be carried out through an online process without a face-to-face meeting. However, the digital world made the safest way to break the chain of spreading the coronavirus outbreak because getting an education is students' right without neglecting their health and mental safety. Digital technology which greatly helps the teacher using the learning media throughout applications can facilitate the relationship between teachers and students in the learning process, even though many obstacles and adjustments were made than the previous face to face learning.